Factors Related To Myths In Exclusive Breastfeeding At The Working Area Of Community Health Center In Banda Aceh - Rahmi, Nuzulul; Andriani, Melda (Universitas Ubudiyah Indonesia, 2017)
Selection of IUD contraceptive methods especially in Indonesia during the last few years tends to decrease demand. These factors include physical, psychological, socio-cultural and religious factors, education level, knowledge, environment, economy, needs, service tariff, and support of husband / family. The purpose of this study was to analyze the factors related to the interests of family planning acceptors using the IUD in Keude Panga Village Panga District 2017. This research is analytic, with cross sectional approach, the population in this study is all KB acceptor in Keude Panga Village Panga Subdistrict totaling 175 people. Sampling technique is done by quota sampling, the number of samples obtained 35 people. The data were collected on May 13th until 26th of May 2017. The data were analyzed using Chi-Square Test with 95% (P <0,05) significance. The result of the research shows that there is a correlation between mothers knowledge level with KB acceptor interest in using IUD with P value = 0,027, there is relation between family economic level with KB acceptor interest in using IUD with P value = 0,001. there is a relationship between husband support with KB acceptor interest in using IUD with P value = 0,007, there is relation between social culture with KB acceptor interest in using IUD with value P = 0,009. Conclusion in this study there is a meaningful relationship between knowledge, family economic level, husband support and socio-culture with interest of KB acceptors using IUD. Expected for the development of science so that the results of this study can be used as a reference in the development of better science and to conduct further research on contraceptive devices in the womb.Keywords:Â Knowledge, Education, Economic Level, Husband Support, Socio-Culture